Plan estratégico de comunicación para la carrera de Comunicación Social UPS, Quito - Lozano Ortiz, Paola Cristina (2014)
The following Thesis Project is a communication proposal about the “Strategic Communication Plan for the UPS-Quito Social Communication Career”. It includes a complete theoretic frame, where human communication history, communication concepts, guide lines of the Habermas Communicative Actions Theory, the Harold Lasswell Functionalism and the Shannon Lineal Theory of Information, are described. Finally, organizational communication elements are defined. Also, career characteristics are highlighted through historical facts, mission, vision, beneficiaries, academic profile, “Week of Communication”, organization charts and the academic curricula, with the objective to emphasize this one academic choice among others of the competence.